Conteúdo jurídico da eficiência administrativa: uma análise lógico-semântica e pragmática - Cabral, Flávio Garcia (2017)
This thesis deals with the legal content of the principle of administrative efficiency before the Brazilian legal system. Although it is a legal norm produced by the interpretation of the constitutional text, Jurisprudence has given little importance to this administrative figure, which makes its meaning, at least in the way that it has been mainly construed, mostly ambiguous, fluid, vague and with difficult pragmatic application. It is precisely because of the neglect often given to administrative efficiency in the doctrinal field, as well as its difficulty of application, due to the absence of an adequate conceptualization, that this work intends to construct a meaning to the administrative efficiency that is constitutionally adequate and that it has a formal coherence that is able to bring a minimum of objectivity to the interpretation / application of the principle. In order to investigate what its legal content would be, it will adopt the perspective of the philosophy of language and the gyro-linguistic movement, more precisely the Logical-Semantic Constructivism, investigating the administrative efficiency by the syntactic, semantic and pragmatic plans. At the end of the research, it is established that the general and abstract norm of administrative efficiency is a methodological and procedural one, which obliges those who execute the administrative function to, when exercising this activity, involving direct administrative costs, choose the best means (those that are least onerous to the Public Administration, both in relation to other existing means and in relation to the intended purpose) that are capable of achieving the intended legal purpose for the benefit of the administered. This normative construction allows, with the division of three maxims of administrative efficiency (effectiveness, economicity and cost-effectiveness), the interpreters / applicators to give effectiveness to this legal norm with a minimum of security and objectivity